Effects of the use of the BAKE mobile application as an Educative instrument for teaching content for preschool education to Shipibo people in the community of Cantagallo, Lima, Peru - Yahuarcani, I.O. (2020)
This document includes the experience in the design, development and validation of a mobile application conceptualized as an instrument for basic teaching and self-learning of the Shipibo - Konibo language. It was created to be used in Bilingual Educative Institutions of preschool level, located in the Peruvian native communities.This App is intended to support the different education gaps in Shipibo-Konibo communities. The App name is BAKE that means child in Shipibo-Konibo language. It works offline and it has been developed for mobile devices with android operative system, considering they would be used in the remote Shipibo-Konibo communities.As part of the validation processes, a comparison test between the use of the application and the use of traditional education in Cantagallo community in Lima (the only Shipibo-Konibo community in Lima) has been developed. The results have been favorable and capabilities have even been identified in the reduction of gaps and overcoming existing limitations in traditional education in Bilingual Educative Institutions.